(untitled) - Thapar, Romila (New Delhi, 1978)
This seminal work by one of India s most eminent historians will be of invaluable use to scholars interested in the study of ancient societies, tradition and culture in the context of social formations, and broadly history.
Keywords: India,India,Ấn Độ,Ấn Độ,Ấn Độ,India; History,History,Nền văn Minh,Lịch sử,Lịch sử,Civilization; To 324 B.C,Từ năm 324 TCN